ANALISIS EFISIENSI PENYALURAN PEMBIAYAAN BAITUL QIRADH DI KOTA BANDA ACEH - SUKMA, KINANTI TIFA (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
ABSTRACTÂ This study aims to determine the efficiency of Baitul Qiradh in Banda Aceh in 2012-2015. The research type used in analysis quantitative descriptive by balanced panel data method.The target sample of this research is active Baitul Qiradh in Banda Aceh. The data used in this research is secondary data from annual financial reporting in 2012-2015. Data analysis was performed using Data Envelopment Analysis method to find the value of each Baitul Qiradh efficiency, and processing the data using program DEAP version 2.1.The results of this research indicate that Baitul Qiradh in Indonesia that is able to achieve perfect efficiency value both CRS and VRS from 2012-2015 there were only 4 Baitul Qiradh, namely Baitul Qiradh Amanah, Baitul Qiradh Amanah Nanggroe, Baitul Qiradh Surya Madinah, and Baitul Qiradh BIMA.Â Keywords: Efficiency, Baitul Qiradh, Data Envelopment Analyis (DEA)